Molecular allergology approach to allergic diseases in the paediatric age - Zaffiro Alessandra; Zennaro Danila; Alessandri Claudia; Mari Adriano (BMC, 2009)
Abstract Identification, characterization, and purification of allergens are essential for the structural and immunologic studies needed to understand how these molecules induce specific IgE antibody production by the human immune system. Advances in molecular biology techniques have led to the production of recombinant allergens having constant properties, allowing detection of specific IgE directed against different molecular components of an allergenic source. Presence of homologous allergens in different sources is the reason for cross-reaction. Molecule-based diagnostic tools can lead to better interpretation of poly-sensitizations, observed by ST and in vitro tests using allergenic extracts as they were made before. Some examples IgE sensitization to major genuine allergens and panallergens will be presented.